Useful of Clap Hand Games for Optimalize Cogtivite Aspects in Early Childhood Education - Mohammad Fauziddin; Mufarizuddin Mufarizuddin (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
Playing is a learning method that best suits learning in early childhood. The clap hand games is one of the types of play that is applied in Early Childhood Education. The purpose of education in early childhood is to develop six aspects of its development namely; aspects of religious and moral norms, aspects of the physical and motor, aspects of cognition, aspects of the emotional social, aspects of language and aspects of art. This study aimed to know the utilization of deep pat game on improving aspects of cognitive in early childhood. The subjects of this study were children of group B Taman Kanak-Kanak (TK) Flamboyan Mekar Tapung District Kampar regency a number of 14 girls and 8 boys. Data collection Technic used is documentation, questionnaire, and interview. This research involves the Ikatan Guru Taman Kanak-Kanak Indonesia (IGTKI) Tapung District to gain input in the development of game pat in order to obtain results. The results of the analysis showed that 86% of children could increase aspects of cognitive development